A phase II multi-strata study of lurbinectedin as a single agent or in combination with conventional chemotherapy in metastatic and/or unresectable sarcomas. (February 2020) - Cote, Gregory M.; Choy, Edwin; Chen, Tianqi; Marino-Enriquez, Adrian; Morgan, Jeffrey; Merriam, Priscilla; Thornton, Katherine; Wagner, Andrew J.; Nathenson, Michael J.; Demetri, George; George, Suzanne
Abstract: Chemotherapy objective response rates (ORRs) in metastatic soft tissue sarcoma (STS) are typically 20–40% with median progression-free survival (PFS) less than 6 months. Lurbinectedin is a new anticancer agent under investigation. The primary objective of this three-arm, phase II study was to determine the disease control rate (DCR = ORR + stable disease [SD]) at 24 weeks of lurbinectedin alone or with chemotherapy in STS. Eligible patients included adults with ≤2 prior cytotoxic therapies. Study cohorts were: stratum A (StrA; anthracycline-naive), lurbinectedin/doxorubicin; stratum B (StrB; prior anthracycline), lurbinectedin/gemcitabine; stratum C (StrC; prior anthracycline/gemcitabine) lurbinectedin monotherapy. Each stratum was analysed separately by Simon two-stage design. Forty-two patients were accrued (StrA = 20, StrB = 10, StrC = 12) including leiomyosarcoma [LMS] (n = 20), synovial sarcoma [SS](n = 4), malignant peripheral nerve sheath tumour (n = 3) and other STS histologies (n = 15). For StrA there were seven partial responses (PR) plus one stable disease (SD) at 24 weeks. For StrB, two patients met the 24-week DCR including one PR (leiomyosarcoma) and one SD (desmoplastic small round cell tumour [DSRCT]). StrB did not continue to the second stage. In StrC, no patients met the primary end-point. Median progression-free survival (PFS) was: StrA = 4.2 months (90% CI 1.4–7.8), StrB = 1.7 months (90% confidence interval (CI) 1.0–7.4), and StrC = 1.3 months (90% CI 1.1–3.0). Lurbinectedin as a single agent or with chemotherapy was well tolerated with haematologic adverse events (AE's) as the most common toxicity. There were no treatment-related deaths. The combination of lurbinectedin/doxorubicin reached the DCR end-point with seven PR and one patient with SD (ORR 35.0%, 24-week DCR 40.0%). Evidence of drug benefit was seen in leiomyosarcoma, dedifferentiated liposarcoma (DDLS), myxoid liposarcoma (MLS), synovial sarcoma (SS), and desmoplastic small round cell tumour (DSRCT). Trial registration: clinicaltrials.gov; NCT02448537 Highlights: Seven of 20 patients treated with lurbinectedin/doxorubicin had partial responses. Preliminary activity was seen in LMS, DDLPS, myxLPS, synovial sarcoma, and DSRCT. The regimen was well-tolerated with most adverse events (AE) at grade 1–2. Grade 3–4 AEs were primarily cytopenias with only 2 episodes of fever-neutropenia.